Efektivitas Metode Pembelajaran Audio Visual pada Siswa SD Kelas 3 untuk Memahami Kisah Tokoh Perjanjian Lama - Fransiska Adel Lewar; Jesica Cindini Br. Sembiring; Karolina Suwul; Intansakti Pius X (Jurnal Pendidikan Agama dan Teologi, 2024)
This research aims to determine the effectiveness of the audio-visual method for grade 3 elementary school students in understanding Old Testament character material, including the stories of Jacob, Joseph and Moses. This research uses a direct observation method with the aim of knowing the learning situations that occur, especially in understanding the story material of Old Testament characters. A teacher must provide interesting and fun learning so that children can draw conclusions from the learning. Audio-visual methods can expedite understanding And strengthen memory student so that on Finally expected student can understand learning specifically know channel story And message from story figure The Old Testament includes story Jacob , the story of Joseph, and the story of Moses.